Gingival Pigmentation among E-cigarette Smokers in Vaping Community in Palembang - Muhammad Thareq Afif Sayuti; Sulistiawaty Sulistiawaty; Bambang Nuryadi (Dentistry Study Program, Faculty of Medicine Universitas Sriwijaya, 2021)
Introduction: Gingival pigmentation is a color alteration of gingiva caused by melanin produced by melanocytes. The etiologic factors include genetic, local, and systemic factors. One of the local factors is the smoking habit. The liquid content in e-cigarettes could cause gingival pigmentation. Purpose: To describe gingival pigmentation in electric smokers. Methods: This was a descriptive survey with the cross-sectional approach, involving 35 respondents from the vaping community in Palembang, using consecutive sampling and quota sampling techniques. The research instrument was using a questionnaire on google form to observe the gingival pigmentation. Results: The frequency distribution of gingival pigmentation was 82.9% of respondents experienced gingival pigmentation and 17.1% of respondents did not experience gingival pigmentation. Conclusion: Gingival pigmentation was found in most heavy e-cigarette smokers in the vaping community in Palembang. Visually, the color changes in gingiva were darker in dual-use smokers than the e-cigarette smokers alone. However, the difference was not statistically significant.